อิทธิพลรูปแบบที่นั่งห้องเรียนต่อการเรียนรู้ของเด็กเรียนรู้ช้า, The Influence of Classroom Seating Arrangement on Student with Slow Learning - หรรนภา นิพัทธา (Asian Creative Architecture, Art and Design, 2018)
Abstract This research examines the influence of seating arrangements on performance of student with learning difficulty (Slow-learner). The research focuses on how different types of seating pattern do effect students’ behaviors by investigating physical environments of Ban Hin Lat school. Non-participant observation was adopted with the target group interview, including 15 slow-learners from grades 4 to 5. Students’ behaviors were recorded during their learning activities, improving slow-learning symptom, both reading and writing in Thai language. According to 4 patterns of classroom seating arrangement, there are 2 patterns reducing learner’s concentration. The average amount of behaviors occurred in accordance with different seating patterns as follows; 1) patterns 1st and 3rd with 2 types of pathway; the front and side of the seats being visible and 2) patterns 2nd and 4th with the pathway on a side of the seats. The result shows that students’ seats should be arranged for minimizing visibility of the pathways and moments, and this can help them increase learning concentration. Keywords: Learning Difficulty, Seating Pattern, Classroom